Florus et le Psautier. La lettre à Eldrade de Novalèse - Bogaert, Pierre-Maurice (Revue bénédictine, 2009)
Florus composed some poems on the Psalms and drew the plan of an ideal Latin Psalter in a letter to Eldradus, abbot of Novalesa. Our sources are the letter of Florus, a poem joined to it, and the Chronicon Novaliciense. Two Psalters must be considered: the Psalter sent by Florus to Eldradus, and the Psalter which Eldradus intended to copy according to the instructions of Florus. One of the distinctive features noted by Florus is the absence of v. 18-20 in the Ps 102 iuxta Hebraeos. Those verses are missing also in the Hebrew column of the two columns Psalter in the Bible of Seo de Urgel. Theodulf might be the missing link between Florus and the Bible of Urgel. — An appendix proposes a list of double Psalters, as a codex or as part of a Bible.